Low‐Frequency Ultrasound Sensitive Piezo1 Channels Regulate Keloid‐Related Characteristics of Fibroblasts - Zixi Jiang; Ziyan Chen; Yantao Xu; Hui Li; Yixin Li; Lanyuan Peng; Han Shan; Xin Liu; Huayi Wu; Lisha Wu; Dan Jian; Juan Su; et al. (Advanced Science, 2024)
Abstract Keloids are benign fibroproliferative tumors that severely diminish the quality of life due to discomfort, dysfunction, and disfigurement. Recently, ultrasound technology as a noninvasive adjuvant therapy is developed to optimize treatment protocols. However, the biophysical mechanisms have not yet been fully elucidated. Here, it is proposed that piezo‐type mechanosensitive ion channel component 1 (Piezo1) plays an important role in low‐frequency sonophoresis (LFS) induced mechanical transduction pathways that trigger downstream cellular signaling processes. It is demonstrated that patient‐derived primary keloid fibroblasts (PKF), NIH 3T3, and HFF‐1 cell migration are inhibited, and PKF apoptosis is significantly increased by LFS stimulation. And the effects of LFS is diminished by the application of GsMTx‐4, the selective inhibitor of Piezo1, and the knockdown of Piezo1. More importantly, the effects of LFS can be imitated by Yoda1, an agonist of Piezo1 channels. Establishing a patient‐derived xenograft keloid implantation mouse model further verified these results, as LFS significantly decreased the volume and weight of the keloids. Moreover, blocking the Piezo1 channel impaired the effectiveness of LFS treatment. These results suggest that LFS inhibits the malignant characteristics of keloids by activating the Piezo1 channel, thus providing a theoretical basis for improving the clinical treatment of keloids.